If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 4) = 3(x + 2) Reorder the terms: 7(4 + x) = 3(x + 2) (4 * 7 + x * 7) = 3(x + 2) (28 + 7x) = 3(x + 2) Reorder the terms: 28 + 7x = 3(2 + x) 28 + 7x = (2 * 3 + x * 3) 28 + 7x = (6 + 3x) Solving 28 + 7x = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 28 + 7x + -3x = 6 + 3x + -3x Combine like terms: 7x + -3x = 4x 28 + 4x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 28 + 4x = 6 + 0 28 + 4x = 6 Add '-28' to each side of the equation. 28 + -28 + 4x = 6 + -28 Combine like terms: 28 + -28 = 0 0 + 4x = 6 + -28 4x = 6 + -28 Combine like terms: 6 + -28 = -22 4x = -22 Divide each side by '4'. x = -5.5 Simplifying x = -5.5
| -6(1+7k)-5=-4K+27 | | -3t+6=60 | | 9p+5=-12 | | 3-5*4= | | -(6x+8)=-8-6x | | 8.2x=10.66 | | -5x+2x=-12 | | 4x+x-3=2 | | 0.3(x+20)-0.05(x-10)=21.5 | | g(x)=17x^9+1 | | y=5x+150 | | (17x-7)+20x+15x+(12x-17)=360 | | 24+4b=6(b+2) | | u=4(2n+33)+5(n+1) | | 2(3z+1)-(2-6)= | | f(0.03)=3x^3-2x^2+6x-4 | | a=(5x-3)(x+2)(2x+3)(3x-2) | | 7-4x=x-8 | | -6+7x=6x-6 | | 2w+w+2w+1=76 | | sin(180)= | | 15.1r=8.9 | | 3p^2-17=0 | | a=(5x-3)(x+2) | | 3x^2+2x=2x+27 | | 4a-3=2a+9 | | 2x^2+3-3=0 | | 8+3x=-3x-4 | | 15x-5+13x+13=180 | | 2(y-7)=5y-32 | | 2(5t-2)=20-(2t) | | 3xwhat=54 |